Jenis Frasa pada Teks Opini Isu Pendidikan dalam Website Pundi.or.id Edisi 2025 - Farid Abrar Suryanata; Deva Reihanasyith Pratama Putra; Muhammad Raffa Yudhanto; Amrizal Muzaki; Valerian Gusty Pradana; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Hasnah Setiani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
This study aims to analyze and identify various types of phrases found in educational opinion texts published on the Pundi.or.id website, 2025 edition. The research is based on the importance of syntactic understanding, particularly the use of phrases, in constructing effective and meaningful sentence structures in opinion texts. A qualitative descriptive method was applied using the observation and note-taking technique. The data were collected by examining, recording, and classifying different types of phrases, including nominal, verbal, adjectival, numerical, and adverbial phrases. The findings reveal that each type of phrase functions differently in shaping sentence meaning and enhancing the clarity of the writer’s arguments. Nominal and verbal phrases were found to dominate the texts, indicating their significant role in presenting ideas and logical reasoning. This research contributes to the development of syntactic studies and provides practical benefits for teachers and students in learning Indonesian, especially in mastering sentence structure and improving opinion writing skills. Furthermore, the study serves as a reference for future linguistic research within the context of digital media and education.